KAJIAN YURIDIS TENTANG PENGENDALIAN LIMBAH BATIK DI KOTA YOGYAKARTA - , RIFMA DARA NINGGAR ([Yogyakarta] : Universitas Gadjah Mada, 2014)
1 batik industry is one of Indonesia's cultural heritage has been recognized internationally that need to be preserved. The existence of the batik industry, mostly small and micro industries (SMEs), in addition to having the benefit of the economy for the people but on the other hand its existence still have environmental impacts of waste pollution resulting from the production process. For the batik industry needs to be encouraged into the industry that is efficient, clean and environmentally friendly. The legal basis for the management and control of industrial pollution batik is Law No. 32 of 2009 on Protection and Management of the Environment, more specifically stipulated in the Regulation of the Minister of Environment No. 03 Year 2010 on Wastewater Quality Standard For Industrial Area, and in particular in the city of Yogyakarta Yogyakarta Governor Regulation No. 7 Year 2010 regarding Liquid Waste Quality Standard for Industrial Activities, Health Care, and Services. 2 Efforts to control and waste management, especially in the city of Yogyakarta batik has not gone well. In the batik waste management, cleaner production fact pattern approach can not be implemented to the fullest because most of the batik industry in the city of Yogyakarta still dispose of waste without treatment processes in accordance with the regulations governing the licensing or that and the lack of concrete action from the relevant authorities to take action against the batik industry which has violated the standards of industrial waste, especially waste batik industry. 3 Obstacles encountered in the control and sewage treatment in the city of Yogyakarta batik is less application of the principles of efficient production (inefficient) use of resources such as water, chemicals, etc. in the industrial processing of batik at this stage of the production process, lack of awareness and understanding as well as training the batik entrepreneurs to conduct clean production, in addition because the batik industry is mostly done by people on their own (home industry) are relatively less educated, and the waste management industry batik is not in accordance with the Standard Operating Procedure (SOP).